The Mainstreaming of the Concept of Legal Protection for Child Labor in Indonesia based on ILO Conventions - Amandha, Asyaffa Ridzqi; Hapsari, Paundria Dwijo; Rivaldi, Muhammad Akmal Rizki; Saputro, Bagus Adi; Cahyani, Anisa; Arifin, Ridwan (Faculty of Law Universitas Negeri Semarang, 2022)
This study delves into the mainstreaming of the concept of legal protection for child labor in Indonesia, drawing insights from the International Labour Organization (ILO) Conventions. Child labor remains a global challenge, impacting the physical, psychological, and social development of children who engage in work during their school years. Beyond mere employment for wages, the issue involves elements of exploitation, hazardous working conditions, and restricted access to education. Certain forms of child labor even qualify as the most intolerable, necessitating urgent attention. The primary objective of this research is to analyze, identify, and compare the legal protection mechanisms for child labor in Indonesia based on the ILO Conventions. Employing a normative legal study methodology, the research employs a dual approach, combining comparative law study and statute analysis. By scrutinizing the legal protection practices within the context of Indonesian law and international law, the study aims to shed light on disparities, commonalities, and potential areas for improvement. Conducting an in-depth examination without relying on fieldwork, the study utilizes a literature review and document study, drawing on various sources from both online and printed materials. Through this comprehensive exploration, the research seeks to contribute to a nuanced understanding of the mainstreaming of legal protections for child labor in Indonesia. By highlighting key findings, this study aims to inform policy discussions, foster awareness, and facilitate the development of more effective measures to safeguard the rights and well-being of children involved in labor activities in the Indonesian context.